Analysis of the operation of an industrial reforming furnace based on plant data and process simulation - Giovanni Morales-Medina; Oscar Emilio Martínez-González; Haydee Quiroga Becerra (CT&F Ciencia, Tecnología & Futuro)
A fundamental process in the clean-fuels chain corresponds to the steam methane reforming (SMR), which generates the hydrogen needed for production of low-sulphur fuels. The identification of opportunities to increase hydrogen production involves the analysis of variables that affects heat supply in the SMR furnace (preheating and reaction section). This document presents the main results of an analysis of heat supply in an industrial SMR furnace based on both, data analysis and simulation with Aspen HYSYS. To such end, eight-year-process-operation data were collected and analysed with kmeans multivariate algorithm. The simulation was validated with pertinent design data and compared to process data. Next, the simulation was applied to explore the operating surface of the furnace to identify conditions with major hydrogen production. According to the results, the statistical analysis by kmeans divided the data into two operational modes that were representative for the furnace; one of them showed the major H2 production. Similarly, the simulation results suggested that the increase in H2 generation was stabilized with the highest values of both heat and natural gas, tending towards a steady state value.